Age, Period and Cohort Differences Between the Homicide Trends of Canada and the United States - Rennó Santos, Mateus (The British journal of criminology, 2021)
A robust literature has investigated homicide trends in the United States since 1950. The prevalence of homicide in the country almost doubled in the 1960s, remained high until the 1990s and then declined precipitously. Surprisingly, Canada displayed the same trend. We decompose the age, period and cohort effects on the homicide trends of the United States and Canada since 1950, exploring shared effects in light of these countries’ historical and policy differences over the past seven decades. Our study reveals remarkably similar trends and effects in Canada as those previously documented for the United States, despite diverging approaches to criminal justice and to the use of incarceration since the 1950s. We explore these findings and expand on their implications.